Evaluating the efficacy of best practice alerts to improve Clostridium difficile early detection in hospital settings: A 6-month interim analysis of the 2-year prospective study - Kaako, Ahmad (Avicenna Journal of Medicine, 2018)
Introduction: Clostridium difficile infection (CDI) is a leading cause of hospital-associated gastrointestinal illness with high burden on the health-care system. Design: Observational, retrospective, prospective, pre- and post-intervention study on the incidence and prevalence rates of CDIs. The primary outcome is the healthcare-onset CDIs (HO-CDIs) incidence rate and proportion. Methods: Best practice alerts (BPAs) for CDI were developed in electronic medical records and released on July 13, 2016. When high-risk patients for CDI are identified, BPAs are triggered requiring nurses to order contact isolation and stool studies followed by other subsequent BPAs encouraging providers to de-escalate antibiotics and order probiotics. Data on admission count, patient-days, CDIs categories prevalence, and incidence rates were collected for the 24-month preintervention and will be collected for the 24-month postintervention period. Results: An interim analysis comparing the data from the first 6-month postintervention period with the average 6-month data of the preintervention period showed that short-term BPAs use is associated with significant increase in the overall CDI infection rate (71.47 vs. 38.38, P < 0.0001), incidence rate (53.81 vs. 28.76, P < 0.0001), overall prevalence rate (1.86 vs. 1.32, P = 0.001), and admission prevalence rate (1.10 vs. 0.70, P < 0.0001). Despite the observed overall shift from HO toward CO; no statistically significant difference in the HO-CDI event number and proportion was detected (28 [21.4%] vs. 22 [29.1%], P = 0.094). Conclusion: Short-term BPAs use is associated with significant increase in the overall CDI incidence and prevalence along with a non-statistically significant decline in HO-CDI proportion. Final analysis with full sample size is essential to provide a better picture about the long-term effect.
Keywords: Best practice alert; Clostridium difficile; hospital-acquired infection